Preparation and application of polymer composite material for scattering and absorbing high-energy blue light

Through high-speed mixing and ultra-high-speed nanoshear dispersion technology of high-refractive inorganic material particles, polymer composite materials that scatter and absorb high-energy blue light were prepared, which solved the problem of insufficient transmittance of existing blue light products and achieved blue light Effective scattering and absorption reduces the harm of blue light to the human body.

CN119161713APending Publication Date: 2024-12-20SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411527840.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing anti-blue light products have insufficient blue light transmittance, which cannot effectively prevent the harm of blue light to the human body, and it is difficult to disperse inorganic material particles into nanometer sizes and evenly disperse them in polymer matrix.

Method used

The particles of inorganic material with high refractive index are used to form polymer composites that scatter and absorb high-energy blue light through high-speed mixing and ultra-high-speed nanoshear dispersion technology, ensuring that the particle size is distributed within the range of 30-800nm, and by adjusting the material thickness and particles The ratio can achieve differentiated refraction and absorption of blue light.

Benefits of technology

It significantly reduces the transmittance of blue light and the relative maximum power in the spectral power distribution, reduces the potential harm of blue light to the human body, and ensures color rendering performance, providing a safer and healthier lighting environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161713A_ABST
    Figure CN119161713A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a polymer composite material for scattering and absorbing high-energy blue light. The inorganic particle material contained in the composite material comprises at least one of inorganic material submicron particles and nanometer particles; when the types of the contained inorganic material submicron particles and the contained inorganic material nanoscale particles reach or exceed two types, the following characteristics are further included: the diameters of the various inorganic material submicron particles and the various inorganic material nanoscale particles are different, and the mass parts of the inorganic material submicron particles and the various inorganic material nanoscale particles in the total mass are different; and the inorganic material nano-scale particles and the inorganic material sub-micron-scale particles are made of the same or different materials, and the refractive indexes of the inorganic material sub-micron-scale particles and the inorganic material nano-scale particles are different due to the material difference of the inorganic material sub-micron-scale particles and the inorganic material nano-scale particles. The blue-light-proof glass can be widely applied to the aspects of eye protection illumination, liquid crystal display, blue-light-proof glasses / films, sun shading and the like, and has the effects of scattering and absorbing blue light, so that the harm caused by the blue light is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optoelectronic materials, and in particular to the preparation and application of a polymer composite material capable of scattering and absorbing high-energy blue light. Background Art

[0002] As people today spend a long time indoors, they are exposed to radiation from artificial light sources at close range and at high frequency. The radiation level and proportion of blue light from artificial light sources are both high, which increases the time people are exposed to blue light. People have found that blue light from digital devices is the same as blue light produced by solar radiation. Blue light mainly damages cells through photochemical effects and can have similar effects on the skin. Long-term exposure to blue light can cause pigmentation, aging, sensitivity and dryness on the skin. At present, skin damage caused by blue light is mainly manifested in causing skin pigmentation and skin photoaging, so the radiation from artificial light sources cannot be ignored. The harm of blue light to the skin and protective measures have attracted more and more attention, and it is very necessary to block blue light.

[0003] At present, the blue light transmittance of the anti-blue light products on the market is large, which is not enough to prevent the harm of blue light to the human body. The key point of the technology is mainly in the technology of inorganic material particle micronization. First of all, the key is how to disperse the inorganic material particles into nanometer size, and make the inorganic nano-particle materials be mixed and evenly dispersed in the polymer matrix, and keep the nano-particles in a dispersed state without agglomeration. Facts have proved that the use of some single inorganic particle materials dispersion technology, such as ultrasonic dispersion, high-speed stirring dispersion, these technologies are not enough to disperse the inorganic material particles into nanometer size, let alone keep the nano-particle dispersion state in the polymer matrix. In order to make the inorganic nanometer and submicron particle materials evenly dispersed in the polymer matrix, first of all, the inorganic nanometer and submicron material must be able to be distributed in the dispersion liquid in the form of particle suspension dispersion, and then added to the polymer according to the corresponding method, and ensure that the material particles are dispersed and evenly distributed in the polymer with the required particle size. Moreover, the anti-blue light product should have different material mass percentages of inorganic particles, different material refractive indices of inorganic particles and different particle sizes of inorganic particles to effectively prevent the harm of blue light to the human body. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned shortcomings and deficiencies of the prior art and to provide a preparation and application of a polymer composite material that scatters and absorbs high-energy blue light.

[0005] The present invention ensures that the material particles are dispersed and evenly distributed in the polymer with the required particle size, and enables the polymer composite material that scatters and absorbs high-energy blue light to have different material mass fractions of inorganic particles, different material refractive indices of inorganic particles and different particle sizes of inorganic particles, so as to prepare blue light protection products with different thicknesses, which can not only scatter and absorb high-energy blue light from the light source, weaken blue light radiation, and avoid damage to human eyes and skin, but also do not affect the color rendering effect.

[0006] The polymer composite material for scattering and absorbing high-energy blue light of the present invention has the functions of scattering and absorbing blue light, and its performance parameters include: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤60%; the relative maximum power (relative power peak) of the blue light spectrum in the spectral power distribution in the spectrum measurement is ≤0.7, the blue light proportion is ≤3.5%, and the color rendering index is ≥90; the composite material contains inorganic material particles with high refractive index, wherein the refractive index of the inorganic material particles is ≥1.900; and the particle size distribution of these inorganic material particles is in the range of 30-800nm.

[0007] The present invention is achieved through the following technical solutions: A preparation method for a polymer composite material that scatters and absorbs high-energy blue light comprises the following steps: 1) Preparation of inorganic material particle dispersion suspension Step 1, mixing the solution and the surfactant at a high speed according to a mass ratio, then adding the inorganic material particles, fully soaking and mixing in a stirring container for 1-2 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 to a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 30 to 60 times, the speed of the emulsifier is 3000-6000 rpm, to form a uniformly dispersed emulsion, and the inorganic material particles have a particle size D90 of 300-800nm; Step 3, then add the emulsion to an ultra-high-speed nano shearing disperser (commercially available), the ultra-high-speed nano-dispersing machine has a rotation speed of 10000-14000 rpm and a maximum linear speed of 66M / S. The ultra-high-speed shearing nano-dispersing machine ultra-finely shears and finely disperses the agglomerated large-particle inorganic material particles, first depolymerizes the inorganic material particles into inorganic material particles with a submicron particle size, and controls the processing conditions of the ultra-high-speed shearing nano-dispersing machine: the rotation speed is 8000-10000 rpm, the processing time is 1-3 hours, and the inorganic material submicron particle dispersion suspension with a particle size of D90 of 200-600nm is obtained. In terms of mass fractions, the raw material dosage in this step is as follows: 70-100 parts of solution, 3-15 parts of surfactant, and 5-30 parts of inorganic material particles; Step 4, adding 1-5 parts of surfactant to the inorganic material submicron particle dispersion suspension of step 3, and controlling the processing conditions of the ultra-high speed shear nano-disperser: the speed is 10000-14000 rpm, and the processing time is 1-3 hours, to obtain an inorganic material nano-particle dispersion suspension with a particle size D90 of 80-110 nm; Alternatively, after the mixed solution obtained in step 1, the processing of step 3 is directly performed, the mixed solution is added to an ultra-high speed shear nano-disperser and fully sheared and dispersed for 2-4 hours to obtain an inorganic material submicron particle dispersion suspension with a particle size D90 of 200-600nm, and 1-5 parts of a surfactant are added and fully sheared and dispersed for 4-6 hours to obtain an inorganic material nanoparticle dispersion suspension with a particle size D90 of 80-110nm; Step 5, mixing and matching an inorganic material submicron particle dispersion suspension and an inorganic material nanoparticle suspension dispersion according to a mass ratio of (1-3): (1-3) to select at least one of them, to obtain an inorganic material particle mixed dispersion suspension; the inorganic material particle mixed dispersion suspension contains inorganic material submicron particles and nanoparticles, and the mass fraction of the inorganic material nanoparticles contained is different from that of the inorganic material submicron particles, and the inorganic material nanoparticles are the same or different from the inorganic material submicron particles; The solution in the inorganic material particle mixed dispersion suspension is a solvent-type, non-solvent-type and water-dispersible solution that is compatible with the corresponding base polymer.

[0008] The solvent-based solution in which the polymer composite material that scatters and absorbs high-energy blue light is compatible with the corresponding substrate polymer is selected from at least one of ethanol, isopropanol, acetone, butanone, cyclohexanone, benzene, toluene, ethyl acetate, n-butanol and styrene; The non-solvent type solution is selected from at least one of a polyethylene glycol aqueous solution (polyethylene glycol content is 10-20%) and a polyvinyl pyrrolidone aqueous solution (polyvinyl pyrrolidone content is 10-20%); The water-dispersible solution is selected from deionized water and distilled water; The inorganic material particle mixed dispersion suspension does not produce a chemical reaction with the corresponding base polymer in the polymer composite material that scatters and absorbs high-energy blue light at high temperature; 2) Preparation of polymer composites that scatter and absorb high-energy blue light (1) The substrate polymer particles and the solvent-based inorganic material particle mixed dispersion suspending agent are mixed in a sealed high-speed mixer at high speed, and the surface of the substrate polymer particles is dissolved, so that the inorganic material particles in the inorganic material particle mixed dispersion suspending agent adhere to the surface of the substrate polymer particles. The mixing time is 1-3 hours, the speed is 3000-6000 rpm, and then the temperature is increased to 40-90° C., and the solvent is evaporated while vacuum exhaust is performed. After the materials are fully stirred, dispersed and dried, a premix of the inorganic material particles and the polymer particles is obtained; (2) For the non-solvent type inorganic material particle mixed dispersion suspension, the substrate polymer particles and the non-solvent type inorganic material particle mixed dispersion suspension are first mixed at high speed in a high-speed mixer to make the inorganic material particles in the inorganic material particle mixed dispersion suspension adhere to the surface of the substrate polymer particles. The mixing time is 1-3 hours, the rotation speed is 3000-6000 rpm, and then the temperature is increased to 40-90° C. The non-solvent type solution is evaporated and vacuumed. The materials are fully stirred, dispersed and dried to obtain a premix of inorganic material particles and polymer particles. (3) For the water-dispersible inorganic material particle mixed dispersion suspension, the substrate polymer particles are first added with an adhesive in an amount of 1-5 parts by mass, and then the substrate polymer particles with the adhesive and the water-dispersible inorganic material particle mixed dispersion suspension are mixed at high speed in a high-speed mixer, so that the inorganic material particles in the inorganic material particle mixed dispersion suspension adhere to the surface of the substrate polymer particles, the mixing time is 1-3 hours, the speed is 3000-6000 rpm, and then the temperature is increased to 40-90° C., and the water-dispersible solution is evaporated while being vacuumed. After the materials are fully stirred, dispersed and dried, a premix of the inorganic material particles and the polymer particles is obtained; The adhesive is a plastic plasticizer, a liquid toughening agent (PC liquid toughening agent, PMMA liquid toughening agent, PS liquid toughening agent), a plastic lubricating dispersant (polyethylene wax, liquid paraffin, polymethylsiloxane, stearate); (4) then adding the premix of the inorganic material particles and the polymer particles, the blue light absorber, and the additives to a high-speed mixer and continuing to mix for 0.5-2 hours, and obtaining a polymer blend after sufficient stirring and dispersion; (5) The polymer blend is then added to an extruder for extrusion and granulation, and the melt extrusion process is vacuum exhausted to obtain a polymer composite material that scatters and absorbs high-energy blue light.

[0009] The inorganic material particle mixed dispersion suspension contains inorganic material submicron particles and nanometer particles, and the mass fraction of the inorganic material nanometer particles and the inorganic material submicron particles is different, and the inorganic material nanometer particles and the inorganic material submicron particles are the same or different in material.

[0010] Further preferably, the polymer composite material that scatters and absorbs high-energy blue light is prepared in the form of a masterbatch; Further preferably, the preparation of the polymer composite material that scatters and absorbs high-energy blue light can be achieved by mixing the base polymer, inorganic material particle mixed dispersion suspending agent, blue light absorber and auxiliary agent, adding them to an extruder and directly extruding them to obtain a product of the polymer composite material that scatters and absorbs high-energy blue light.

[0011] It is further preferred that the substrate polymer, blue light absorber, additive, inorganic material submicron particle dispersion suspension and inorganic material nanoparticle dispersion suspension are directly added to the processing equipment in proportion by automatic quantitative delivery to obtain a polymer composite masterbatch or product that scatters and absorbs high-energy blue light.

[0012] In terms of mass fraction, the raw materials used in this step are: 70-100 parts of the substrate polymer, 0.01-2.5 parts of the inorganic material particle mixed dispersion suspending agent, 0.1-1.2 parts of the blue light absorber, and 1-25 parts of the auxiliary agent; The base polymer of the polymer composite material that scatters and absorbs high-energy blue light is selected from at least one of polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polystyrene, transparent polypropylene, transparent polyethylene, polyvinyl chloride, polyurethane, epoxy resin, polyether sulfone, polyether ketone, polyether ether ketone and transparent polymer.

[0013] The inorganic material particles of the polymer composite material that scatters and absorbs high-energy blue light are selected from at least one of high-refractive index materials with a refractive index greater than 1.900: zinc selenide, barium oxide, zinc oxide, zirconium dioxide, copper oxide, ferric oxide, titanium pentoxide, cerium oxide, chromium oxide, zinc sulfide, titanium dioxide, and antimony tin oxide; The surfactant of the polymer composite material that scatters and absorbs high-energy blue light is selected from at least one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, sodium oleate, carboxylates, sulfate ester salts, sulfonates, alkyl aryl phosphates, alkyl benzene sulfonates (sodium dodecylbenzene sulfonate), dialkyl sulfosuccinates, polyoxyethylene alkylphenol ethers, sorbitol alkylates, polycarboxylates, poly(meth)acrylic acid derivatives, maleic anhydride copolymers, and polycarboxylic acid polymers; The blue light absorber is selected from quantum dot materials that absorb blue light: cadmium selenide quantum dots, cadmium telluride quantum dots, cadmium sulfide quantum dots, indium selenide quantum dots; The auxiliary agent of the polymer composite material that scatters and absorbs high-energy blue light is at least one of 0.3-3 parts of lubricant, 0.1-5 parts of plasticizer, 0-1.2 parts of light diffuser, 0.2-6 parts of antioxidant, and 0.1-5 parts of toughening agent; Lubricants: stearic acid, paraffin, polyethylene wax; Plasticizers: DINP (diisononyl phthalate), DIDP (diisodecyl phthalate), DOP, ATBC; Light diffuser: acrylic light diffuser, styrene light diffuser, acrylic resin light diffuser, silicone microsphere light diffuser; Antioxidants: 1010, 168; Toughening agent: polycarbonate toughening agent, polymethyl methacrylate toughening agent, polystyrene toughening agent, transparent polypropylene toughening agent; The application of the polymer composite material for scattering and absorbing high-energy blue light of the present invention is as follows: (1) Adding a light diffusing agent to the polymer composite material that scatters and absorbs high-energy blue light, extruding the plate, and embossing the plate on one or both sides with an embossing roller to effectively block the transmittance of blue light, thereby obtaining a light diffusing plate product with high light transmittance; (2) Extruding the polymer composite material for scattering and absorbing high-energy blue light onto a press plate. Since the particle size of the polymer composite material for scattering and absorbing high-energy blue light is in the range of 30nm-800nm, the blue light with a wavelength of 380-500nm is reflected, refracted, diffracted and absorbed, and a strong scattering and absorption effect is produced on the blue light, thereby obtaining a product with high light transmittance and high blue light scattering effect simulating a blue sky effect; (3) injection molding the light diffusion composite material to obtain a blue light blocking polymer light diffusion molded product; (4) The light-diffusing composite material is formed by vacuum molding or blow molding to obtain a blue light-proof polymer light-diffusing molded product.

[0014] Compared with the prior art, the present invention has the following advantages and effects: The present invention has the following significant features, which are mainly reflected in the particle size, thickness, composition and concentration of inorganic particles: 1. By using high refractive index granular materials and a variety of different granular materials, the present invention achieves differentiated refractive index regulation of incident light. This difference not only causes blue light to be scattered to different angles, but also produces different degrees of scattering effects through precise control, thereby easily adjusting the blue light transmission blocking rate to meet the needs of different application scenarios.

[0015] 2. The present invention utilizes the difference in particle size between inorganic submicron particles and inorganic nanoparticles, and combines their different mass fractions to achieve precise control of incident blue light. This design enables the present invention to selectively block harmful wavelengths of blue light, effectively reduce the proportion of blue light in the spectrum, and thus significantly reduce the potential harm of blue light to the human body.

[0016] 3. The thickness variation of the inorganic particle material plays a key role in the present invention. By adjusting the thickness of the material, we can affect the transmittance of blue light and increase the path length it travels. This causes the blue light to be refracted multiple times inside the particles, effectively blocking the transmission of the blue light, thereby enhancing the scattering intensity of the blue light and reducing its transmittance.

[0017] 4. Under the premise of ensuring normal color display, the present invention ensures high color rendering performance of the spectrum by fine-tuning the proportion of blue light. At the same time, we use a polymer composite material that can scatter and absorb high-energy blue light to further enhance the scattering and absorption effect of blue light, thereby effectively reducing the relative maximum power of the blue light spectrum in the spectral power distribution, and significantly reducing the potential harm of high-energy blue light to human health. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the spectral transmittance measurement of the polymer composite product that scatters and absorbs high-energy blue light in Example 1 (thickness 1.5 mm).

[0019] Figure 2 is the relative maximum power of the blue light spectrum of Example 1 (thickness 1.5 mm).

[0020] Figure 3 This is the spectral transmittance measurement of the polymer composite product that scatters and absorbs high-energy blue light in Example 2 (thickness 1.5 mm).

[0021] Figure 4 is the relative maximum power of the blue light spectrum of Example 2 (thickness 1.5 mm).

[0022] Figure 5 This is the spectral transmittance measurement of the polymer composite product that scatters and absorbs high-energy blue light in Example 3 (thickness 1.5 mm).

[0023] Figure 6 is the relative maximum power of the blue light spectrum of Example 3 (thickness 1.5 mm).

[0024] Figure 7 This is the spectral transmittance measurement of the polymer composite product that scatters and absorbs high-energy blue light in Example 4 (thickness 1.5 mm).

[0025] Figure 8 is the relative maximum power of the blue light spectrum of Example 4 (thickness 1.5 mm).

[0026] Fig. 9 This is the spectral transmittance measurement of the polymer composite product that scatters and absorbs high-energy blue light in Example 5 (thickness 1.5 mm).

[0027] Fig.10is the relative maximum power of the blue light spectrum of Example 5 (thickness 1.5 mm).

[0028] Fig.11 It is the light transmittance of the comparative example (thickness 1.5mm).

[0029] Fig.12 is the relative maximum power of the blue light spectrum (thickness 1.5 mm). DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with specific embodiments.

[0031] Example 1 1) Preparation of inorganic material nanoparticle zinc selenide dispersion suspension in butanone: Step 1, 70 parts of solution butanone and 3 parts of surfactant sodium hexametaphosphate are mixed at high speed, and then 5 parts of inorganic material particles zinc selenide are added, and the mixture is fully infiltrated and mixed in a stirring container for 1 hour to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 30, the speed of the emulsifier is 3000 rpm, to form a uniformly dispersed emulsion, and the particle size of the inorganic material particles obtained is D90 of 760 nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material particles. The inorganic material particles are first deagglomerated into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 8000 rpm, the processing time is 1 hour, and the inorganic material submicron particle dispersion suspension with a particle size D90 of 206 nm is obtained. Step 4, adding 1 part of sodium hexametaphosphate as a surfactant to the inorganic material submicron particle dispersion suspension of step 3, and controlling the processing conditions of the ultra-high speed shear nano-disperser: the speed is 10000 rpm, the processing time is 1 hour, to obtain an inorganic material nano-particle dispersion suspension with a particle size D90 of 102 nm; 2) Preparation of inorganic material submicron zinc oxide particle butanone dispersion suspension: Step 1, 70 parts of solution butanone and 3 parts of surfactant sodium hexametaphosphate are mixed at high speed, and then 5 parts of inorganic material particles of zinc oxide are added, and the mixture is fully infiltrated and mixed in a stirring container for 1 hour to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 30, the speed of the emulsifier is 3000 rpm, to form a uniformly dispersed emulsion, and the particle size of the inorganic material particles obtained is D90 of 740 nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for full shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material particles. The inorganic material particles are first deagglomerated into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 8000 rpm, the processing time is 1 hour, and a butanone dispersion suspension of inorganic material submicron particles of zinc oxide with a particle size D90 of 420 nm is obtained.

[0032] 3) Mixing a butanone dispersion suspension of inorganic material submicron particles of zinc oxide and a butanone dispersion suspension of inorganic material nanoparticles of zinc selenide in a ratio of 1:1 to obtain an inorganic material particle mixed butanone dispersion suspension; 4) 70 parts of the polycarbonate substrate polymer particles and 0.4 parts of the inorganic material particle mixed dispersion suspending agent in a butanone solution are mixed in a sealed high-speed mixer at high speed to dissolve the surface of the substrate polymer particles, so that the inorganic material particles in the inorganic material particle mixed dispersion suspending agent adhere to the surface of the substrate polymer particles. The mixing time is 1 hour, the speed is 3000 rpm, and then the mixture is heated to 40° C., vacuumed and exhausted, and fully stirred and dispersed to obtain a premix of the inorganic material particle mixed dispersion agent and the polymer particles; 5) then adding the premix, 0.1 part of blue light absorber cadmium selenide quantum dots, 0.3 part of stearic acid, 0.1 part of DIDP, 0.1 part of silicone microsphere light diffuser, 0.2 part of antioxidant 1010, 0.2 part of antioxidant 168, and 0.1 part of polycarbonate toughening agent, to a high-speed mixer and continuing mixing for 0.5 hour, and obtaining a polymer blend after sufficient stirring and dispersion; 6) The polymer blend is then added to an extruder for extrusion and granulation, and the melt extrusion process is vacuum-exhausted to obtain a polymer composite material that scatters and absorbs high-energy blue light.

[0033] 7) The polymer composite material that scatters and absorbs high-energy blue light is injection molded to obtain an eye protection lampshade. Since the particle size of the polymer composite material that scatters and absorbs high-energy blue light is in the range of 30nm-800nm. Since the blue light with a wavelength of 380-500nm is reflected, refracted, diffracted and absorbed by the inorganic material submicron particles and nanometer particles, a strong scattering and absorption effect is produced on the blue light, which plays an effective function of protecting the eyes. It has a transmission function for other longer wavelengths, and a product with high light transmittance and blue light protection effect is obtained.

[0034] Measurement of 1.5mm thick sample: UV-visible spectrophotometer Agilent cary60 Measurement of spectral transmittance of products: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤60%, such as Figure 1 As shown; The spectral power distribution of the product measured by the spectral illuminance meter SFIM-400 is as follows: Figure 2 As shown: the relative maximum power of the blue light spectrum in the spectral power distribution is 0.692; the proportion of blue light in the spectrum measurement of the product is 3.5%, and the color rendering index is ≥90.

[0035] Measurement of 2.5mm thick samples: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤53%; the relative maximum power of the blue light spectrum in the spectral power distribution is 0.632; the proportion of blue light in the spectrum measurement of the product is 3.2%, and the color rendering index is ≥90.

[0036] Example 2 1) Preparation of ethanol dispersion suspension of inorganic material nanoparticle titanium dioxide: Step 1, 90 parts of ethanol solution and 8 parts of sodium dodecylbenzene sulfonate surfactant are mixed at high speed, and then 20 parts of inorganic material particles of titanium dioxide are added, and fully infiltrated and mixed in a stirring container for 2 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 40, the speed of the emulsifier is 5000 rpm, to form a uniformly dispersed emulsion, and the particle size of the inorganic material particles obtained is D90 of 630 nm nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material. The inorganic material particles are first deagglomerated into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 9000 rpm, the processing time is 2 hours, and an ethanol dispersion suspension of inorganic material submicron particles with a particle size D90 of 220 nm is obtained.

[0037] Step 4, adding 3 parts of sodium dodecylbenzene sulfonate as a surfactant to the inorganic material submicron particle dispersion suspension of step 3, and controlling the processing conditions of the ultra-high speed shear nano-disperser: the speed is 12000 rpm, the processing time is 2 hours, to obtain an inorganic material nano-particle ethanol dispersion suspension with a particle size D90 of 104 nm; 2) Preparation of ethanol dispersion suspension of inorganic material submicron particles of zirconium dioxide: Step 1, 90 parts of solution ethanol and 8 parts of surfactant sodium dodecylbenzene sulfonate are mixed at high speed, and then 20 parts of inorganic material particles of zirconium dioxide are added, and fully infiltrated and mixed in a stirring container for 2 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 40, the speed of the emulsifier is 5000 rpm, to form a uniformly dispersed emulsion, and the particle size of the inorganic material particles obtained is D90 of 690nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material particles, and deagglomerates the inorganic material particles into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 9000 rpm, the processing time is 2 hours, and an ethanol dispersion suspension of inorganic material submicron particles of zirconium dioxide with a particle size D90 of 380 nm is obtained.

[0038] 3) Mixing an ethanol dispersion suspension of inorganic material submicron titanium dioxide particles and an ethanol dispersion suspension of inorganic material nanometer zirconium dioxide particles in a ratio of 2:1 to obtain an inorganic material particle mixed ethanol dispersion suspension; 4) Mixing 90 parts of the PMMA substrate polymer particles and 0.8 parts of the ethanol dispersion suspending agent with the inorganic material particles in a sealed high-speed mixer at high speed, dissolving the substrate polymer particles on the surface, and making the inorganic material particles in the inorganic material particle mixed dispersion suspending agent adhere to the surface of the substrate polymer particles. The mixing time is 2 hours, the speed is 4500 rpm, and then the mixture is heated to 60° C., evacuated and exhausted, and fully stirred and dispersed to obtain a premix of the inorganic material particle mixed dispersion agent and the polymer particles; 5) Then the premix, 0.2 parts of blue light absorber cadmium sulfide quantum dots, 1 part of polyethylene wax, 1 part of DOP, 0.3 parts of antioxidant 1010 and 0.3 parts of 168, and 2 parts of polymethyl methacrylate toughening agent were added to a high-speed mixer and continued to mix for 1 hour, and the polymer blend was obtained after sufficient stirring and dispersion; 6) The polymer blend is then added to an extruder for extrusion and granulation, and the melt extrusion process is vacuum-exhausted to obtain a polymer composite material that scatters and absorbs high-energy blue light.

[0039] 7) Extruding the polymer composite material that scatters and absorbs high-energy blue light onto a press plate, and embossing the plate on one or both sides with an embossing roller. Since the particle size of the polymer composite material that scatters and absorbs high-energy blue light is in the range of 30nm-500nm, the blue light with a wavelength of 360-500nm is reflected, refracted, diffracted and absorbed, and a strong scattering and absorption effect is produced on the blue light, so that the product is similar to the diffuse effect of the sky on the blue light under the oblique illumination of the light, and a scene simulating the blue sky is produced, so that a product simulating the blue sky effect with high light transmittance and high blue light scattering is obtained; Measurement of 1.5mm thick sample: UV-visible spectrophotometer Agilent cary60 Measurement of spectral transmittance of products: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤58%, such as Figure 3 As shown; The spectral power distribution of the product measured by the spectral illuminance meter SFIM-400 is as follows: Figure 4 As shown: the relative maximum power of the blue light spectrum in the spectral power distribution is 0.673; the blue light ratio is 3.2%. Color rendering index ≥90, Measurement of 2.5mm thick samples: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤52%; the relative maximum power of the blue light spectrum in the spectral power distribution is 0.612; the proportion of blue light in the spectrum measurement of the product is 3.0%, and the color rendering index is ≥90.

[0040] Example 3 1) Preparation of deionized water dispersion suspension of inorganic material nanoparticles titanium pentoxide: Step 1, 100 parts of deionized water and 10 parts of a surfactant polycarboxylate are mixed at high speed, and then 30 parts of inorganic material particles of titanium pentoxide are added, and the mixture is fully infiltrated and mixed in a stirring container for 4 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 60, the speed of the emulsifier is 6000 rpm, to form a uniformly dispersed emulsion, and the particle size of the inorganic material particles obtained is D90 of 710 nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material. The inorganic material particles are first deagglomerated into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 10,000 rpm and the processing time is 3 hours to obtain a titanium pentoxide aqueous dispersion of inorganic material submicron particles with a particle size D90 of 330 nm.

[0041] Step 4, adding 5 parts of a surfactant polycarboxylate to the inorganic material submicron particle dispersion suspension of step 3, and controlling the processing conditions of the ultra-high speed shear nano-disperser: a speed of 14000 rpm, a processing time of 3 hours, to obtain a titanium pentoxide aqueous dispersion suspension of inorganic material nano-particles with a particle size D90 of 106 nm; 2) Preparation of deionized water dispersion suspension of inorganic material submicron barium oxide particles: Step 1, 100 parts of deionized water and 10 parts of a surfactant polycarboxylate are mixed at high speed, and then 30 parts of inorganic material particles of barium oxide are added, and the mixture is fully soaked and mixed in a stirring container for 4 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 60, the speed of the emulsifier is 6000 rpm, to form a uniformly dispersed emulsion, and the particle size of the inorganic material particles obtained is D90 of 720 nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material particles, and deagglomerates the inorganic material particles into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 10,000 rpm, the processing time is 3 hours, and an aqueous dispersion suspension of inorganic material submicron particles of barium oxide with a particle size D90 of 402 nm is obtained.

[0042] 3) Mixing the water-dispersible suspension of inorganic material nanoparticles of titanium pentoxide and the water-dispersible suspension of inorganic material submicron particles of barium oxide in a ratio of 3:1 to obtain an inorganic material particle mixed water-dispersible suspension; 4) First, 100 parts of polystyrene base polymer particles and 5 parts of PS liquid toughening agent are uniformly mixed to make the PS liquid toughening agent adhere to the surface of the polystyrene particles, and then 0.6 parts of the inorganic material particle mixed water dispersible suspension agent are added, and the mixture is sealed and mixed at high speed on a sealed high-speed mixer to make the inorganic material particles in the inorganic material particle mixed dispersible suspension agent adhere to the surface of the base polymer particles. The mixing time is 3 hours, the speed is 6000 rpm, and then the mixture is heated to 90° C., vacuumed and exhausted, and the premix of the inorganic material particle mixed dispersant and the polymer particles is obtained after sufficient stirring and dispersion; 5) Then add the premix, 0.3 parts of blue light absorber cadmium telluride quantum dots, 1.5 parts of stearic acid, 1.5 parts of DINP (diisononyl phthalate), and 0.8 parts of styrene-based light diffuser, 2 parts of antioxidant 1010 and 2 parts of 168 were added to a high-speed mixer and mixed for 2 hours to obtain a polymer blend after sufficient stirring and dispersion; 5) The polymer blend is then added to an extruder for extrusion and granulation, and the melt extrusion process is vacuum exhausted to obtain a polymer composite material that scatters and absorbs high-energy blue light.

[0043] 6) The polymer composite material for scattering and absorbing high-energy blue light is extruded into a sheet plate, and embossed on one side or both sides by an embossing roller to obtain a blue light-proof polymer light-diffusing sheet product, which is applied to blue light-proof products such as classroom lighting fixtures, office lighting fixtures, and public lighting fixtures.

[0044] Measurement of 1.5mm thick sample: UV-visible spectrophotometer Agilent cary60 Measurement of spectral transmittance of products: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤53%, such as Figure 5 As shown; The spectral power distribution of the product measured by the spectral illuminance meter SFIM-400 is as follows: Figure 6 As shown: the relative maximum power of the blue light spectrum in the spectral power distribution is 0.685; the blue light ratio is 3.0%. Color rendering index ≥90, Measurement of 2.5mm thick samples: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤48%; the relative maximum power of the blue light spectrum in the spectral power distribution is 0.616; the proportion of blue light in the spectrum measurement of the product is 2.9%, and the color rendering index is ≥90.

[0045] Example 4 1) Preparation of polyethylene glycol non-solvent suspension of inorganic material nanoparticles anatase titanium dioxide: Step 1, 100 parts of polyethylene glycol non-solvent solution with a solid content of 10% and 10 parts of sodium pyrophosphate as a surfactant are mixed at high speed, and then 15 parts of anatase titanium dioxide particles of inorganic material are added, and the mixture is fully infiltrated and mixed in a stirring container for 2 hours to form a mixed solution; Step 2: Add the mixed solution to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser ultra-finely shears and finely disperses the agglomerated large particles of inorganic material. The inorganic material particles are first deagglomerated into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 10,000 rpm and the processing time is 3 hours to obtain an inorganic material submicron particle polyethylene glycol anatase titanium dioxide non-solvent suspension with a particle size D90 of 230 nm.

[0046] Step 3, adding 3 parts of sodium pyrophosphate as a surfactant to the inorganic material submicron particle polyethylene glycol anatase titanium dioxide non-solvent suspension of step 2, and dispersing it by an ultra-high speed shear nano-disperser, wherein the control processing conditions of the ultra-high speed shear nano-disperser are: a speed of 14000 rpm, a processing time of 5 hours, and obtaining an inorganic material nano-particle polyethylene glycol anatase titanium dioxide non-solvent suspension with a particle size D90 of 103 nm; 2) Preparation of polyethylene glycol non-solvent suspension of inorganic material submicron particle zinc oxide: Step 1, 100 parts of polyethylene glycol non-solvent solution with a solid content of 20% and 10 parts of sodium pyrophosphate as a surfactant are mixed at high speed, and then 20 parts of inorganic material particles of zinc oxide are added, and the mixture is fully infiltrated and mixed in a stirring container for 2 hours to form a mixed solution; Step 2: Add the mixed solution to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser ultra-finely shears and finely disperses the agglomerated large particles of inorganic material particles, and deagglomerates the inorganic material particles into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 10,000 rpm, the processing time is 3 hours, and a polyethylene glycol non-solvent suspension of inorganic material submicron particles of zinc oxide with a particle size D90 of 380 nm is obtained.

[0047] 3) Mixing a polyethylene glycol non-solvent suspension of inorganic material nanoparticles of anatase titanium dioxide and a polyethylene glycol non-solvent suspension of inorganic material submicron particles of zinc oxide in a ratio of 3:1.5 to obtain a polyethylene glycol non-solvent suspension of inorganic material particles; 4) First, 100 parts of polystyrene substrate polymer particles and 2.4 parts of polyethylene glycol non-solvent type suspension agent mixed with the inorganic material particles are mixed in a sealed high-speed mixer at high speed to make the inorganic material particles in the polyethylene glycol non-solvent type suspension agent adhere to the surface of the substrate polymer particles. The mixing time is 2 hours and the speed is 3000 rpm. Then, the mixture is heated to 80° C., vacuumed and exhausted, and fully stirred and dispersed to obtain a premix of the inorganic material particles mixed with the polyethylene glycol dispersant and the polymer particles. 5) Then, the premix, 1.2 parts of blue light absorber cadmium telluride quantum dots, 3 parts of stearic acid, 3 parts of DOP, 1.2 parts of styrene-based light diffuser, antioxidant: 3 parts of 1010, 3 parts of 168, and 5 parts of polystyrene toughening agent are added to a high-speed mixer and mixed for 2 hours, and the polymer blend is obtained after sufficient stirring and dispersion; 6) The polymer blend is then added to an extruder for extrusion and granulation, and the melt extrusion process is vacuum exhausted to obtain a polymer composite masterbatch that scatters and absorbs high-energy blue light.

[0048] 7) The polystyrene plastic is mixed with a polymer composite masterbatch that scatters and absorbs high-energy blue light in a ratio of 100:4 to extrude a sheet, which is embossed on both sides by an embossing roller to obtain a blue light-proof polymer light-diffusing sheet product, which is used in the blue light-proof products of classroom lighting fixtures.

[0049] Measurement of 1.5mm thick sample: UV-visible spectrophotometer Agilent cary60 Measurement of spectral transmittance of products: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤55%, such as Figure 7 As shown; The spectral power distribution of the product measured by the spectral illuminance meter SFIM-400 is as follows: Figure 8 As shown: the relative maximum power of the blue light spectrum in the spectral power distribution is 0.673; the blue light ratio is 3.1%. The color rendering index is ≥90.

[0050] Measurement of 2.5mm thick samples: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤51%; the relative maximum power of the blue light spectrum in the spectral power distribution is 0.628; the proportion of blue light in the spectral measurement of the product is 2.8%, and the color rendering index is ≥90.

[0051] Example 5 1) Preparation of ethanol dispersion suspension of inorganic material nanoparticle barium oxide: Step 1, 90 parts of solution ethanol and 8 parts of surfactant sulfonate are mixed at high speed, and then 20 parts of inorganic material particles of barium oxide are added, and the mixture is fully infiltrated and mixed in a stirring container for 2 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 50, the speed of the emulsifier is 5500 rpm, to form a uniformly dispersed emulsion, and the inorganic material particles have a particle size D90 of 660nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material. The inorganic material particles are first deagglomerated into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 8000 rpm and the processing time is 3 hours to obtain an inorganic material submicron particle barium oxide ethanol dispersion suspension with a particle size D90 of 230 nm.

[0052] Step 4, adding 4 parts of surfactant sulfonate to the inorganic material submicron particle dispersion suspension of step 3, and controlling the processing conditions of the ultra-high speed shear nano-disperser: speed 10000 rpm, processing time 2 hours, to obtain an inorganic material nano-particle barium oxide ethanol dispersion suspension with a particle size D90 of 105 nm; 2) Preparation of ethanol dispersion suspension of inorganic material submicron particles of rutile titanium dioxide: Step 1, 90 parts of ethanol solution and 5 parts of surfactant sulfonate are mixed at high speed, and then 20 parts of inorganic material particles rutile titanium dioxide are added, and the mixture is fully infiltrated and mixed in a stirring container for 3 hours to form a mixed solution; Step 2, adding the mixed solution of step 1 into a three-stage high shear dispersing emulsifier pump (commercially available) for cyclic emulsification dispersion, the number of cycles is 40, the speed of the emulsifier is 4000 rpm, to form a uniformly dispersed emulsion, and the inorganic material particles have a particle size D90 of 560nm; Step 3. Finally, the emulsion is added to an ultra-high speed nano shearing disperser (commercially available) for sufficient shearing and dispersion. The ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material particles, and deagglomerates the inorganic material particles into inorganic material particles with a submicron particle size. The processing conditions of the ultra-high speed shearing nano disperser are controlled as follows: the speed is 9000 rpm, the processing time is 2.5 hours, and an ethanol dispersion suspension of inorganic material submicron particles of rutile titanium dioxide with a particle size D90 of 420 nm is obtained.

[0053] 3) Mixing an ethanol dispersion suspension of inorganic material nanoparticles of barium oxide and an ethanol dispersion suspension of inorganic material submicron particles of rutile titanium dioxide in a ratio of 2.5:1 to obtain an inorganic material particle mixed ethanol dispersion suspension; 4) 90 parts of the transparent plastic PMMA substrate polymer particles, 0.2 parts of cadmium telluride quantum dots, 1 part of ATBC, 1 part of polyethylene wax, 0.5 parts of silicone microsphere light diffuser, 0.3 parts of antioxidant 1010, 0.3 parts of 168, 5 parts of polymethyl methacrylate toughening agent, and 0.8 parts of mixed ethanol dispersing suspending agent are directly added into the extrusion equipment by automatic quantitative conveying according to the mass ratio to obtain a light diffusing sheet of a polymer composite material that scatters and absorbs high-energy blue light.

[0054] 5) The polymer composite light-diffusing sheet is formed by vacuum molding or blow molding to obtain a polymer light-diffusing molded product that scatters and absorbs blue light.

[0055] Measurement of 1.5mm thick sample: UV-visible spectrophotometer Agilent cary60 Measurement of spectral transmittance of products: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤42%, such as Fig. 9 As shown; The spectral power distribution of the product measured by the spectral illuminance meter SFIM-400 is as follows: Fig.10 As shown, the relative maximum power of the blue light spectrum in the spectral power distribution is 0.613; the blue light accounts for 2.9%. Color rendering index ≥90, Measurement of 2.5mm thick samples: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤38%; the relative maximum power of the blue light spectrum in the spectral power distribution is 0.586; the proportion of blue light in the spectral measurement of the product is 2.6%, and the color rendering index is ≥90.

[0056] Comparative Example 1) First, 100 parts of polystyrene base polymer particles are added with 1.5 parts of stearic acid, 1.5 parts of DINP (diisononyl phthalate); 0.8 parts of styrene type light diffuser, 2 parts of antioxidant 1010, and 2 parts of 168; add them into a high-speed mixer and continue mixing for 2 hours, and obtain a polymer blend after sufficient stirring and dispersion; 2) The polymer blend is then added to an extruder for extrusion and granulation, and the melt extrusion process is vacuum-exhausted to obtain a polymer composite material.

[0057] 3) Extruding the polymer composite material into a sheet plate, and embossing one side or both sides of the sheet plate with an embossing roller to obtain a polymer light diffuser plate product.

[0058] Measurement of 1.5mm thick sample: UV-visible spectrophotometer Agilent cary60 Measurement of spectral transmittance of products: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤81%, such as Fig.11 As shown; The spectral power distribution of the product measured by the spectral illuminance meter SFIM-400 is as follows: Fig.12 As shown, the relative maximum power of the blue light spectrum in the spectral power distribution is 0.998; the blue light accounts for 5.2%. Color rendering index ≥90, Measurement of 2.5mm thick samples: within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤80%; the relative maximum power of the blue light spectrum in the spectral power distribution is 0.998; the proportion of blue light in the spectral measurement of the product is 5.1%, and the color rendering index is ≥90.

[0059] Blue light, as a component with shorter wavelength and higher energy in the visible spectrum, may pose a risk to the retina if directly exposed for a long time, induce eye discomfort such as visual fatigue and dry eyes, and even interfere with sleep quality. To this end, modern science and technology has introduced advanced low-blue light technology, which can effectively filter out a portion of high-energy harmful blue light in the range of 380-500 nanometers by precisely controlling the spectral distribution, while ensuring that the color rendering index of the light source remains at a high level, close to the comfort of natural light.

[0060] At the same time, within the wavelength range of 380-500nm, the blue light transmittance within the unit wavelength interval of blue light is ≤60%, ensuring a significant reduction in harmful blue light components in the light source output, and further avoiding the risk of retinal damage and visual fatigue caused by long-term exposure to high-intensity blue light.

[0061] In measuring the quality of light sources, a color rendering index (Ra) higher than 90 is a sign of high-quality light sources. It can truly reproduce the colors of objects under natural light and provide users with a more realistic and vivid visual experience.

[0062] It is worth noting that the relative maximum power (blue light peak) in the blue light spectrum is reduced to less than 0.7, which means that the blue light energy is significantly reduced, which directly reduces the potential threat of blue light to the eyes. The high energy of blue light can easily cause difficulty in eye focusing and accelerate the aging of retinal cells, but after this treatment, these problems can be effectively alleviated.

[0063] In addition, the reduced intensity of blue light also reduces its inhibitory effect on melatonin secretion, which helps maintain a normal sleep cycle. At the same time, low-peak blue light significantly reduces glare, making the lighting environment warmer and softer, suitable for long-term reading, work and other scenes.

[0064] In summary, when the energy peak in the blue light spectrum is reduced from 1 to 0.7, it means that the light energy is reduced by about 30%. The reduction in the proportion of blue light and the control of blue light transmittance together constitute a safer lighting environment. These improvements not only meet but even exceed industry safety standards, especially the blue light protection products made of polymer composite materials that scatter and absorb high-energy blue light, which perform particularly well, providing users with a more intimate and healthy lighting solution.

[0065] As described above, the present invention forms a polymer composite material system that scatters and absorbs high-energy blue light by adding environmentally friendly nano-sized inorganic nano-material particles and sub-micronized inorganic material particles. The system has the functions of scattering and absorbing high-energy blue light, reducing the relative maximum power of the blue light spectrum in the spectral power distribution, and blocking the transmittance of high-energy blue light to a large extent. The polymer composite material that scatters and absorbs high-energy blue light is different from ordinary polymer anti-blue light materials in the following four aspects: 1. The size effect of particle size and its influence on the scattering and absorption of blue light In optics and materials science, the size effect of particle size has a significant impact on the scattering and absorption of light. When blue light (wavelength between 380nm and 500nm) is incident on particles with different particle sizes, both scattering and absorption occur.

[0066] Scattering effect: Based on scattering theory, when light interacts with particles inside a substance, it is scattered in multiple directions. Since blue light has a shorter wavelength, the scattering phenomenon is more significant when it interacts with particles of smaller size (such as 30-110nm). This is because when the size of the particle is comparable to the wavelength of light, the interaction between the wave nature of light and the particle will lead to a significant scattering effect, causing the blue light to diffuse in multiple directions.

[0067] Absorption effect: When the particle size increases (such as 110-800nm), the absorption of light gradually becomes important. According to the principles of quantum mechanics, the molecular or atomic structure of a substance will interact with the electromagnetic radiation field of the incident light. When the wavelength of blue light matches the specific energy level difference in the molecular or atomic structure of the substance, the photon energy will be absorbed by the electron, resulting in energy level transition and electron excitation. Therefore, particles with larger particle sizes can absorb blue light more effectively, causing the shorter wavelength blue light to be weakened or disappear.

[0068] It is worth noting that scattering and absorption are not mutually exclusive, but can occur simultaneously. When the particle size is comparable to the wavelength of blue light, the scattering phenomenon is more significant; and when the particle size increases to be close to or larger than the wavelength of blue light, the absorption effect gradually becomes dominant. This interaction makes particles of different sizes have different effects on the scattering and absorption of blue light.

[0069] When preparing polymer composites that scatter and absorb high-energy blue light, effective control of blue light can be achieved by adjusting the particle size ratio of the inorganic particulate material. For example, when the particle size distribution is in the range of 30-110nm, the material has a strong scattering effect on blue light; when the particle size distribution is in the range of 110-800nm, it relies more on reflection and absorption to attenuate blue light. Appropriately matching the number of particles of different particle sizes not only enriches the distribution of particle size, but also effectively increases the scattering and absorption capacity of blue light, thereby reducing the transmittance of high-energy blue light and achieving the purpose of blue light protection.

[0070] 2. Refraction Mechanism of Inorganic Material Particles The refractive mechanism of inorganic material particles is reflected in the fact that the refractive index of the material has an important influence on the propagation behavior of light in it. Although the refractive index does not directly affect the actual propagation speed of light in the material, it is a key parameter that describes the degree of deflection of light when it enters another medium from one medium. A higher refractive index means that the light will be deflected more when entering the material, which will affect the propagation direction and scattering characteristics of the light.

[0071] Particles of different materials have different refractive indices, and these differences lead to different scattering and absorption behaviors of light. Since the wavelength of blue light is relatively short, it is more easily affected by the refractive index of the material. When blue light enters a material particle with a high refractive index from a medium, the light is deflected due to the difference in refractive index, and the propagation direction of the blue light changes accordingly. Therefore, material particles with different refractive indices will have different degrees of influence on the scattering of blue light. Generally, material particles with a higher refractive index will cause a greater degree of deflection of blue light, a wider scattering range, and possibly a stronger scattering intensity.

[0072] In addition, different particle materials have different refractive indices for different wavelengths of light. These differences make the high refractive index material have a stronger ability to scatter light. Based on this principle, polymer composites that scatter and absorb high-energy blue light use a variety of high refractive index nano or submicron particle materials. These materials have a high refractive index for incident light, thereby effectively increasing the scattering and absorption of blue light, forming a richer scattering effect. Generally speaking, materials with higher refractive indices tend to have stronger blue light scattering intensity.

[0073] 3. Different thickness of materials affects the transmittance of blue light When considering the transmittance of blue light, we cannot ignore the critical factor of material thickness. When blue light passes through the same type of material but with different thicknesses, its transmittance will be significantly different. Specifically, when the material is thinner, the path experienced by blue light is relatively short and it is less affected by scattering, refraction, and absorption, so its transmittance is higher. However, when the thickness of the material increases, the distance that blue light needs to travel becomes longer, which makes it easier for it to interact with particles inside the material, experience more scattering and refraction, and is also more easily absorbed by the material. These effects together lead to a decrease in the transmittance of blue light. Therefore, it can be clearly said that the thickness of the material is one of the important factors that determine the transmittance of blue light.

[0074] 4. Inorganic material particles weaken the power of high-energy blue light.

[0075] When high-energy blue light shines on inorganic material particles, the size of these particles is similar to or smaller than the wavelength of blue light, which causes significant light scattering. The mechanism of light scattering is that when light encounters the inhomogeneity of particles or interfaces, the light changes direction at these interfaces, and part of the blue light energy is scattered in various directions and no longer propagates along the original path. This process causes the blue light energy to disperse and weaken, thereby reducing the total power of high-energy blue light.

[0076] In addition to light scattering, inorganic material particles can also weaken the power of high-energy blue light by absorbing energy. For larger particles, the absorption and scattering effects usually occur simultaneously. Inorganic material particles can absorb part of the blue light energy and convert it into other forms of energy, such as heat energy or emission of light of different wavelengths, depending on the characteristics of their composition and structure. This energy conversion process reduces the amount of blue light propagating in the material, thereby further reducing the power of high-energy blue light.

[0077] The attenuation effect of inorganic material particles on high-energy blue light power is affected by many factors. First, the particle size is one of the key factors. When the particle size is comparable to the wavelength of blue light, the scattering effect is most significant. Secondly, the material composition and composition of the particles determine its ability to absorb blue light, and different materials have different absorption rates for blue light. In addition, the concentration of particles and the thickness of the material will also affect the scattering and absorption effects of blue light. The higher the particle concentration and the greater the thickness, the more particles the blue light encounters in the material, and the more obvious the scattering and absorption effects.

[0078] By precisely controlling these characteristics of inorganic material particles, precise regulation of high-energy blue light power can be achieved. Inorganic material particles with specific particle size, composition and concentration are added to effectively reduce the transmittance of high-energy blue light and the relative maximum power of the blue light spectrum in the spectral power distribution, thereby protecting the eyes from blue light damage.

[0079] The above four anti-blue light properties are unique to polymer composite materials that scatter and absorb high-energy blue light. Ordinary anti-blue light materials cannot achieve the above-mentioned anti-blue light properties unique to polymer composite materials that scatter and absorb high-energy blue light because they do not fully have the scattering and absorption effects on blue light.

[0080] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polymer composite material that scatters and absorbs high-energy blue light, characterized in that The steps include: S1, preparation of inorganic material particle dispersion suspension; S1-1, mixing the solution and the surfactant at a high speed according to a mass ratio, adding the inorganic material particles, and fully soaking and mixing them in a stirring container for 1-2 hours to form a mixed solution; S1-2, adding the mixed liquid of step S1-1 to a three-stage high shear dispersing emulsifier pump for cyclic emulsification dispersion, the number of cycles is 30 to 60, the speed of the emulsifier is 3000-6000 rpm, to form a uniformly dispersed emulsion, and the inorganic material particles have a particle size D90 of 300-800nm; S1-3, then add the emulsion to the ultra-high speed nano shearing disperser, the ultra-high speed nano disperser speed is 10000-14000 rpm, the maximum linear speed is 66M / S; the ultra-high speed shearing nano disperser performs ultra-fine shearing and fine dispersion on the agglomerated large particles of inorganic material particles, first depolymerizes the inorganic material particles into inorganic material particles with submicron particle size, and controls the processing conditions of the ultra-high speed shearing nano disperser: the speed is 8000-10000 rpm, the processing time is 1-3 hours, and the inorganic material submicron particle dispersion suspension with a particle size D90 of 200-600nm is obtained; in terms of mass parts, the raw material usage in this step is in mass parts: 70-100 parts of solution, 3-15 parts of surfactant, and 5-30 parts of inorganic material particles; S1-4, adding 1-5 parts of surfactant to the inorganic material submicron particle dispersion suspension of step S1-3, and controlling the processing conditions of the ultra-high speed shear nano-disperser: the speed is 10000-14000 rpm, and the processing time is 1-3 hours, to obtain an inorganic material nano-particle dispersion suspension with a particle size D90 of 80-110 nm; S1-5, mixing and matching an inorganic material submicron particle dispersion suspension and an inorganic material nanoparticle suspension dispersion in a mass ratio of (1-3): (1-3) to obtain at least one of them, to obtain an inorganic material particle mixed dispersion suspension; The solution in the inorganic material particle mixed dispersion suspension is a solvent-based, non-solvent-based and water-dispersible solution that is compatible with the corresponding base polymer; S2, Preparation of polymer composites that scatter and absorb high-energy blue light: S2-1, mixing the substrate polymer particles and the solvent-based inorganic material particle mixed dispersion suspending agent in a sealed high-speed mixer at high speed, dissolving the surface of the substrate polymer particles, and making the inorganic material particles in the inorganic material particle mixed dispersion suspending agent adhere to the surface of the substrate polymer particles, the mixing time is 1-3 hours, the speed is 3000-6000 rpm, and then heating to 40-90° C., while the solvent is volatilized, vacuum exhaust is drawn, and the materials are fully stirred, dispersed and dried to obtain a premix of the inorganic material particles and the polymer particles; S2-2, for the non-solvent type inorganic material particle mixed dispersion suspension, firstly, the substrate polymer particles and the non-solvent type inorganic material particle mixed dispersion suspension are mixed at high speed in a high-speed mixer, so that the inorganic material particles in the inorganic material particle mixed dispersion suspension adhere to the surface of the substrate polymer particles, the mixing time is 1-3 hours, the rotation speed is 3000-6000 rpm, and then the temperature is increased to 40-90° C., and the non-solvent type solution is evaporated while vacuum exhaust is drawn, and the materials are fully stirred, dispersed and dried to obtain a premix of the inorganic material particles and the polymer particles; S2-3, for the water-dispersible inorganic material particle mixed dispersion suspension, first add the substrate polymer particles to the adhesive in an amount of 1-5 parts by mass, and then mix the substrate polymer particles with the adhesive and the water-dispersible inorganic material particle mixed dispersion suspension on a high-speed mixer at high speed, so that the inorganic material particles in the inorganic material particle mixed dispersion suspension adhere to the surface of the substrate polymer particles, the mixing time is 1-3 hours, the speed is 3000-6000 rpm, and then the temperature is increased to 40-90° C., and the water-dispersible solution is evaporated while being vacuumed and exhausted, and the materials are fully stirred, dispersed, and dried to obtain a premix of the inorganic material particles and the polymer particles; S2-4, then adding the premix of inorganic material particles and polymer particles, blue light absorber, and additives to a high-speed mixer and continuing to mix for 0.5-2 hours, and obtaining a polymer blend after sufficient stirring and dispersion; S2-5, adding the polymer blend into an extruder for extrusion and granulation, and performing vacuum exhaust during the melt extrusion process to obtain a polymer composite material that scatters and absorbs high-energy blue light.

2. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The inorganic material particle mixed dispersion suspension contains inorganic material submicron particles and nanometer particles, and the mass fraction of the inorganic material nanometer particles and the inorganic material submicron particles is different, and the inorganic material nanometer particles and the inorganic material submicron particles are the same or different in material.

3. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: In S2-5, the polymer composite material that scatters and absorbs high-energy blue light is prepared in the form of a masterbatch; Preparation of polymer composite materials that scatter and absorb high-energy blue light, by mixing substrate polymer, inorganic material particles, a dispersing suspending agent, a blue light absorber and an auxiliary agent, and then adding them to an extruder for direct extrusion molding to obtain a product of the polymer composite material that scatters and absorbs high-energy blue light; Alternatively, the substrate polymer, the blue light absorber, the additive, the inorganic material submicron particle dispersion suspension and the inorganic material nanoparticle dispersion suspension are respectively added directly into the processing equipment in proportion by automatic quantitative conveying to obtain a polymer composite material masterbatch or product that scatters and absorbs high-energy blue light; In terms of mass fractions, the raw materials used in this step are as follows: 70-100 parts of the base polymer, 0.01-2.5 parts of the inorganic material particle mixed dispersion suspending agent, 0.1-1.2 parts of the blue light absorber, and 1-25 parts of the auxiliary agent.

4. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The adhesive is a plastic plasticizer, a liquid toughening agent and / or a plastic lubricating dispersant; The solvent solution is selected from at least one of ethanol, isopropanol, acetone, butanone, cyclohexanone, benzene, toluene, ethyl acetate, n-butanol and styrene; The non-solvent type solution is selected from at least one of a polyethylene glycol aqueous solution and a polyvinyl pyrrolidone aqueous solution; The water-dispersible solution is selected from deionized water and distilled water.

5. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The substrate polymer is selected from at least one of polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polystyrene, transparent polypropylene, transparent polyethylene, polyvinyl chloride, polyurethane, epoxy resin, polyether sulfone, polyether ketone, polyether ether ketone and transparent polymer.

6. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The inorganic material particles are selected from at least one of high refractive index materials with a refractive index greater than 1.900: zinc selenide, barium oxide, zinc oxide, zirconium dioxide, copper oxide, ferric oxide, titanium pentoxide, cerium oxide, chromium oxide, zinc sulfide, titanium dioxide, and antimony tin oxide.

7. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The surfactant is selected from at least one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, sodium oleate, carboxylates, sulfate ester salts, sulfonates, alkyl aryl phosphates, alkyl benzene sulfonates, dialkyl sulfosuccinates, polyoxyethylene alkylphenol ethers, sorbitol alkylates, polycarboxylates, polyacrylic acid derivatives, maleic anhydride copolymers and polycarboxylic acid polymers.

8. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The blue light absorber is a quantum dot material that absorbs blue light, specifically cadmium selenide quantum dots, cadmium telluride quantum dots, cadmium sulfide quantum dots or indium selenide quantum dots.

9. The method for preparing the polymer composite material for scattering and absorbing high-energy blue light according to claim 1, characterized in that: The auxiliary agent is at least one of 0.3-3 parts of lubricant, 0.1-5 parts of plasticizer, 0-1.2 parts of light diffuser, 0.2-6 parts of antioxidant, and 0.1-5 parts of toughening agent; Lubricant: stearic acid, paraffin, polyethylene wax; Plasticizer: DINP, DIDP, DOP or ATBC; Light diffuser: acrylic light diffuser, styrene light diffuser, acrylic resin light diffuser or silicone microsphere light diffuser; Antioxidants: 1010, 168; Toughening agent: polycarbonate toughening agent, polymethyl methacrylate toughening agent, polystyrene toughening agent or transparent polypropylene toughening agent.

10. Application of the polymer composite material for scattering and absorbing high-energy blue light according to any one of claims 1 to 9: A light diffusing agent is added to a polymer composite material that scatters and absorbs high-energy blue light, extruded into a press plate, and embossed on one or both sides by an embossing roller to effectively block the transmittance of blue light, thereby obtaining a light diffusing sheet product with high light transmittance; The polymer composite material for scattering and absorbing high-energy blue light is extruded onto a press plate. Since the particle size of the polymer composite material for scattering and absorbing high-energy blue light is in the range of 30nm-800nm, the blue light with a wavelength of 380-500nm is reflected, refracted, diffracted and absorbed, and the blue light is scattered and absorbed to simulate a product with a blue sky effect; injection molding the light diffusion composite material to obtain a blue light-proof polymer light diffusion molded product; The light diffusion composite material is formed by suction molding and blow molding to obtain a blue light-proof polymer light diffusion molded product.

Citation Information

Cited By

  • Composite light guide film and preparation method and application thereof

    CN120623543A